On Cointegration and Cryptocurrency Dynamics - Georg Keilbar; Yanfen Zhang (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2020)
This paper aims to model the joint dynamics of cryptocurrencies in a nonstationary setting. In particular, we analyze the role of cointegration relationships within a large system of cryptocurrencies in a vector error correction model (VECM) framework. To enable analysis in a dynamic setting, we propose the COINtensity VECM, a nonlinear VECM specification accounting for a varying systemwide cointegration exposure. Our results show that cryptocurrencies are indeed cointegrated with a cointegration rank of four. We also find that all currencies are affected by these long term equilibrium relations. A simple statistical arbitrage trading strategy is proposed showing a great in-sample performance.
Keywords: C00; 330; Cointegration; VECM; Nonstationarity; Cryptocurrencies